Demographic Structure and the Security of Property Rights in Developing Countries – An Empirical Exploration - Philipp Harms; Philipp an de Meulen (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
It is often argued that countries with a high population share of children and young workers should attract large capital inflows from aging industrialized economies. However, many of these countries deter foreign investors by a high risk of creeping or outright expropriation. In this paper we explore whether the correlation between countries' demographic structure and the perceived security of property rights reflects a causal relationship. We show that, once we control for other potential determinants of expropriation risk, the ratio of young to old workers has a positive effect on the perceived security of property rights in low-income countries. This effect is the stronger the more democratic the political system. – – Es wird häufig argumentiert, dass die internationalen Unterschiede zwischen den demografischen Strukturen Anreize für Kapitalmobilität aus alternden und kapitalreichen Industrieländern in Entwicklungs- und Schwellenländer mit einer wachsenden Arbeitsbevölkerung schaffen. Allerdings werden diese Anreize in vielen gering entwickelten Regionen durch ein hohes Risiko direkter und indirekter Enteignung verzerrt. Im vorliegenden Beitrag wird untersucht, ob zwischen den demografischen Strukturen und dem geringen Schutz von Eigentumsrechten ein Kausalzusammenhang besteht. Entgegen der Korrelation zeigen die Ergebnisse der empirischen Analyse, dass es einen positiven Einfluss eines höheren Bevölkerungsanteils junger Individuen auf die Sicherheit der Eigentumsrechte ausländischer Investoren in Entwicklungsländern gibt. Dieser Effekt zeigt sich umso stärker je demokratischer das politische System eines Landes ist.
Keywords: F21; D78; J10; 330; international investment; political economy; expropriation risk; demographics